2012
DOI: 10.1111/j.1474-9726.2012.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

The age‐related increase in low‐grade systemic inflammation (Inflammaging) is not driven by cytomegalovirus infection

Abstract: SummaryAging is accompanied by the development of low-grade systemic inflammation, termed 'inflammaging', characterized by raised serum C-reactive protein (CRP) and pro-inflammatory cytokines. Importantly, inflammaging is implicated in the pathogenesis of several of the major age-related diseases including cardiovascular disease, type 2 diabetes, and dementia and is associated with increased mortality. The incidence of infection with the persistent herpes virus cytomegalovirus (CMV) also increases with age. Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(117 citation statements)
references
References 20 publications
4
109
3
1
Order By: Relevance
“…Although inflammatory response may potentiate cell-induced angiogenesis (Laflamme & Murry, 2011), the overexpression of pro-inflammatory cytokines could further trigger pro-apoptotic signal cascade and suppress the survival of donor cells . Aging-associated inflammatory disorder also contributes to the high risk and progression of senile PAD (Erren et al, 1999;Bartlett et al, 2012). Our present data indicated Sarp may enable a favorable niche for the functional survival of mADSCs through regulation of inflammation.…”
Section: Discussionmentioning
confidence: 52%
“…Although inflammatory response may potentiate cell-induced angiogenesis (Laflamme & Murry, 2011), the overexpression of pro-inflammatory cytokines could further trigger pro-apoptotic signal cascade and suppress the survival of donor cells . Aging-associated inflammatory disorder also contributes to the high risk and progression of senile PAD (Erren et al, 1999;Bartlett et al, 2012). Our present data indicated Sarp may enable a favorable niche for the functional survival of mADSCs through regulation of inflammation.…”
Section: Discussionmentioning
confidence: 52%
“…15,36,[41][42][43][44] Our study provides the first demonstration of a strong relationship between CMV IgG and impaired physical function in HIV infection. Whether CMV alone plays a causative role in the deterioration of physical function or is a marker of another variable that is associated with decreased physical function could not be determined in this study.…”
Section: Cd38mentioning
confidence: 59%
“…It should also be noted that some studies have doubted a role for CMV in immunosenescence and aging‐associated inflammation (Cicin‐Sain et al ., 2011; Bartlett et al ., 2012). However, one of them used a rhesus macaque model of aging (Cicin‐Sain et al ., 2011), where old was defined as up to 26 years, and probably not comparable with the age of our octogenarians.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of them used a rhesus macaque model of aging (Cicin‐Sain et al ., 2011), where old was defined as up to 26 years, and probably not comparable with the age of our octogenarians. The study by Bartlett took CMV seropositivity into consideration, but not T‐cell immunity specifically (Bartlett et al ., 2012). Derhovassian and coworkers have shown that the response to CMV can be very heterogeneous and that immunological control of the virus can contribute to decreased mortality rate (Derhovanessian et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%